The Influence Of Korean Wave, Advertising Attractiveness, And Brand Image On Purchase Decisions For Ultramilkxstraykids Products In South Kalimantan - Stefanie Octasya Effendy; Rifqi Amrulloh; Freddy Jayen; Melania, Melania; Abdul Kadir (Jurnal Ekonomi, 2024)
The aim of this research is to determine the influence of Korean Wave factors, advertising attractiveness, and brand image on purchasing decisions for Ultra Milk advertise the product to 100 people. Research data was collected using a Google Form questionnaire which was distributed via the social media applications Twitter and WhatsApp . The research results show that the independent variables simultaneously have a positive and significant effect on purchasing decisions with a calculated F value (59.441) > F table (2.70) and a value of 0 < 0.05. Partially, the Korean Wave variable has a significant effect on the calculated t value (2.530) > t table (1.98498) with a Sig value. 0.013 < 0.05. Then the advertising attractiveness variable has a significant influence on the calculated value (7.647)> t table (1.98498) with a value of Sig. 0.000 <0.05 . And the brand image variable does not have a significant effect with the calculated value (0.378) < t table (1.98498) with a value of Sig. 0.706 > 0.05. The variable that has a dominant influence on purchasing decisions is the advertising attractiveness variable with a β ( Standardized Coefficients Beta) value of 0.647.